2022
DOI: 10.17951/pjss.2022.55.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Land Use Types on Soil Physico-Chemical Properties in Wolaita Zone, Ethiopia

Abstract: Soils are obviously inconstant and their properties are changing across land use types. Essential soil physico-chemical assets impact the performance of soil and, therefore, information on soil property is important. The objective of the study was to determine effects of different land use systems on soil physico-chemical properties in Wolaita zone, southern Ethiopia. Soil samples were collected from three different land uses, enset (Ensete ventricosum), tef (Eragrostis tef (Zucc.) Trotter) and grass lands. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This might be attributed to the high OM content and anion released from OM competing with P for fixation by Al 3+ and H + cations and release of P through mineralization of OM in the forest land. However, in the forest, P is more or less circulated within the area and not removed from there, and in grazing land, the dung of animals has an impact on available P. In line with this Weldemariam et al (2020); Ekero et al (2022) and most recently Abadeye et al (2023) reported relatively higher and lower available P under forest and cultivated land respectively. Available S was also significantly affected by the difference in land use types.…”
Section: Effect Of Land Use Types On Soil Oc Tnmentioning
confidence: 63%
See 2 more Smart Citations
“…This might be attributed to the high OM content and anion released from OM competing with P for fixation by Al 3+ and H + cations and release of P through mineralization of OM in the forest land. However, in the forest, P is more or less circulated within the area and not removed from there, and in grazing land, the dung of animals has an impact on available P. In line with this Weldemariam et al (2020); Ekero et al (2022) and most recently Abadeye et al (2023) reported relatively higher and lower available P under forest and cultivated land respectively. Available S was also significantly affected by the difference in land use types.…”
Section: Effect Of Land Use Types On Soil Oc Tnmentioning
confidence: 63%
“…On the other hand, the lowest exchangeable Ca 2+ (2.7 cmol+ kg −1 ) and Mg 2+ (1.8 cmol+ kg −1 ) was recorded in cultivated land due to its continuous removal through crop harvest with no or little organic matter input into the soil and high leaching losses when soil is disturbed with intensive cultivation. Dereje (2020); Ekero et al (2022) and most recently Asmare et al (2023) reported that relatively the highest and lowest level of exchangeable Ca 2+ and Mg 2+ was found under natural forest and cultivated land, respectively. Exchangeable K + and Na + content was significantly affected by land use type.…”
Section: Effect Of Land Use Types On Soilmentioning
confidence: 93%
See 1 more Smart Citation
“…The other can be continuous cropping (Ma et al., 2022; Sainju & Alasinrin, 2020) and increased use of inorganic fertilizers (Ge et al., 2018; Sainju & Alasinrin, 2020). High tillage rates (Gu et al., 2021), high rates of inorganic fertilizer applications (particularly ammonium fertilizers), and low levels of organic matter may contribute to low arable land pH levels due to erosion or aluminum toxicity (Desta Ekero et al., 2022). This can be due to erosion, use of ammonium fertilizers, or inappropriate plowing techniques (Negasa, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the administration of the treatments, experimental feld soils were assessed for a number of physicochemical characteristics using the approach described in [28] (Table 3). Te experimental site's mean soil pH was 4.99, which was strongly acidic [29] and ideal for the growth of various vegetable crops.…”
Section: Physicochemical Characteristics Of Soilmentioning
confidence: 99%